A Note on Quadrangular Embedding of Abelian Cayley Graphs - Strapasson, João Eloir; Costa, Sueli Irene Rodrigues; Muniz, Marcelo (Trends in Computational and Applied Mathematics, 2016)
The genus graphs have been studied by many authors, but just a few results concerning in special cases: Planar, Toroidal, Complete, Bipartite and Cartesian Product of Bipartite. We present here a general lower bound for the genus of a abelian Cayley graph and construct a family of circulant graphs which reach this bound.